1984
DOI: 10.1146/annurev.iy.02.040184.001015
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor Cells and Immunoregulation

Abstract: We have described a model system of immunoregulation in which gene products associated with both the major histocompatibility complex and the heavy-chain immunoglobulin gene complex guide a series of cellular interactions. The Igh genetic restrictions may represent the use of internal images of antigen and idiotype as suppressor-T cell receptors. The data indicate that the T-cell and B-cell Igh products are distinct. The T cell-derived idiotype-like determinants are used for suppressor-T cell communications. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0
1

Year Published

1985
1985
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 307 publications
(48 citation statements)
references
References 86 publications
3
44
0
1
Order By: Relevance
“…During the early 1980s, immunologists determined that two cellular mechanisms of tolerance induction could mediate peripheral regulation and the phenomena of induced CD4 + T cell nonresponsiveness. These two mechanisms were MHC-restricted T cell presentation of antigen to other T cells [1] and suppression via thymically derived 'suppressor' T cells [2]. Shortly after the discovery of MHC class II + CD4 + T cells in human peripheral blood (these cells are present in most mammalian species excluding mice [3]) [4,5], Kunkel and his colleagues [6] observed that autoimmune patients have a higher percentage of these cells in peripheral blood than healthy patients.…”
Section: Introductionmentioning
confidence: 99%
“…During the early 1980s, immunologists determined that two cellular mechanisms of tolerance induction could mediate peripheral regulation and the phenomena of induced CD4 + T cell nonresponsiveness. These two mechanisms were MHC-restricted T cell presentation of antigen to other T cells [1] and suppression via thymically derived 'suppressor' T cells [2]. Shortly after the discovery of MHC class II + CD4 + T cells in human peripheral blood (these cells are present in most mammalian species excluding mice [3]) [4,5], Kunkel and his colleagues [6] observed that autoimmune patients have a higher percentage of these cells in peripheral blood than healthy patients.…”
Section: Introductionmentioning
confidence: 99%
“…1). Early on, CD8 ϩ T cells were identified that suppress immune responses through their direct cytotoxicity on antigen-bearing cells or through cryptic suppressor factors that were poorly characterized (2). However, during this early period, there were already hints that the quintessential helper T cells subset, CD4 ϩ T cells, also may have regulatory activity.…”
mentioning
confidence: 99%
“…This was followed by a flurry of activity, identifying several phenotypic markers for the various cell types involved in the suppression of excessive immune responsiveness (CD8 + suppressor effector cells, CD4 + suppressor-inducer cells etc. ), as well as several secreted suppressor factors [10,11]. The whole concept eventually fell into disrepute, mostly because of the lack of reproducible assays for these cells and lack of molecular identification of the factors involved [11,12].…”
Section: The Definition Of Tregsmentioning
confidence: 99%